2020
DOI: 10.1093/cid/ciaa554
|View full text |Cite
|
Sign up to set email alerts
|

High Burden of Bloodstream Infections Associated With Antimicrobial Resistance and Mortality in the Neonatal Intensive Care Unit in Pune, India

Abstract: Background Antimicrobial resistance (AMR) is a growing threat to newborns in low and middle income countries (LMIC). Methods We performed a prospective cohort study in three tertiary Neonatal Intensive Care Units (NICUs) in Pune, India, to describe the epidemiology of neonatal bloodstream infections (BSI). All neonates admitted to the NICU were enrolled. The primary outcome was BSI, defined as positive blood culture. Early on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 38 publications
4
30
1
Order By: Relevance
“…Carbapenem- and/or polymyxin-resistant GNB are common in neonates and pregnant women in several countries as either infections or colonizations, threatening the lives of the affected patients as CR-GNB and PR-GNB are associated with longer hospitalization and higher morbidities and mortalities 29,4648 . Worryingly, many of the studies involved in this review reported on clonal and polyclonal outbreaks and infections of CR-GNB or PR-GNB among neonates in NICUs or colonization of CR-GNB in pregnant women involving pathogenic GNB such as A. baumannii, E. coli, Enterobacter sp ., K. pneumoniae , and P. aeruginosa (Tables S1-S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbapenem- and/or polymyxin-resistant GNB are common in neonates and pregnant women in several countries as either infections or colonizations, threatening the lives of the affected patients as CR-GNB and PR-GNB are associated with longer hospitalization and higher morbidities and mortalities 29,4648 . Worryingly, many of the studies involved in this review reported on clonal and polyclonal outbreaks and infections of CR-GNB or PR-GNB among neonates in NICUs or colonization of CR-GNB in pregnant women involving pathogenic GNB such as A. baumannii, E. coli, Enterobacter sp ., K. pneumoniae , and P. aeruginosa (Tables S1-S3).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not surprising that numerous studies report on CR-GNB- and polymyxin-resistant Gram-negative bacteria (PR-GNB)-infected neonates than colonized ones 20,23,25,26 . Further, there have been abundant reports of clonal and polyclonal CR-GNB outbreaks in neonatal intensive care units (NICUs) globally, claiming the lives of several neonates as a result 18,2729 . This makes neonates more susceptible to CR-GNB and PR-GNB infections with their associated morbidity and mortality 17–20,30 .…”
Section: Introductionmentioning
confidence: 99%
“…Organization-namely, ampicillin, gentamicin, and third generation cephalosporins such as cefotaxime, and even multidrug-resistant (MDR) 4 . A 2020 study of neonatal BSIs in Pune, India reported a high prevalence of AMR with high mortality 3 . Effective interventions are urgently needed to reduce burden of BSIs and death due to AMR pathogens in hospital neonates 5 .…”
Section: Amr Pathogens Exhibit a High Degree Of Resistance To Rst Linmentioning
confidence: 99%
“…In 2017, an estimated 48.9 million incident cases of BSIs were recorded worldwide and 11.0 million BSIs-related deaths were reported, representing 19.7% of all global deaths 2 . It is important that progress in neonatal survival has not kept pace with global reductions in child mortality and neonatal deaths now account for 47% of deaths in children under the age of ve years 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Mortality rates due to bloodstream infection (BSI) range between 12 and 32% in North America and Europe and are even higher in low-and middle-income countries. Mortality is due in part to increasing rates of antimicrobialresistant pathogens (5)(6)(7)(8)(9)(10). Patients infected with resistant pathogens are more likely to receive ineffective empiric antibiotic therapy, which is associated with poor outcomes, including death (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%